Odpowiedzi

2010-03-25T21:06:35+01:00
A) ×/₃+1 =⁵/₆+×/₂ obustronnie *6

6*(x/3)+6*1=6*(5/6)+6*(x/2)
2x+6=5+3x obustronnie -2x
6=5+x obustronnie -5
x=1

b) 2×+3/₅=2-×/₃ +× obustronnie *15
15*2x+15*(3/5)=15*2+15*(-x/3)+15*x
30x+9=30-5x+15x
30x+9=30+10x obustronnie -10x
20x+9=30 obustronnie -9
20x=21 obustronnie :20
x=21/20=(1 i 1/20)=1,05
Najlepsza Odpowiedź!
2010-03-25T21:07:39+01:00
A) ×/₃+1 =⁵/₆+×/₂ / *6
2x+6= 5+ 3x
2x-3x=5-6
-x=-1 /*(-1)
x=1

b) 2×+3/₅=2-×/₃ +× /*15
30x+9=30-5x+15x
30x+5x-15x=30-9
20x=21 /:20
x=21/20
x= 1 i 1/20
1 5 1